Prolonged effect of antibiotic therapy on the gut microbiota composition, functionality, and antibiotic resistance genes’ profiles in healthy stool donors - Karimianghadim, Ramin; Satokari, Reetta; Yeo, Sam; Arkkila, Perttu; Kao, Dina; Pakpour, Sepideh (Frontiers in Microbiology, 2025)
IntroductionFecal microbiota transplantation (FMT) is highly effective in preventing Clostridioides difficile recurrence by restoring gut microbiota composition and function. However, the impact of recent antibiotic use, a key exclusion criterion for stool donors, on gut microbiota recovery is poorly understood.MethodsWe investigated microbial recovery dynamics following antibiotic use in three long-term stool donors from Canada and Finland. Using longitudinal stool sampling, metagenomic sequencing, and qPCR, we assessed changes in bacterial diversity, community composition, microbial functions, the gut phageome, and the risk of transmitting antibiotic-resistant genes (ARGs).ResultsAntibiotics caused lasting disruption to bacterial communities, significantly reducing important taxa like Bifidobacterium bifidum, Blautia wexlerae, Akkermansia muciniphila, Eubacterium sp. CAG 180, and Eubacterium hallii, with effects persisting for months. Functional analyses revealed alterations in housekeeping genes critical for energy production and biosynthesis, with no direct links to key health-related pathways. Antibiotics also disrupted viral populations, decreasing diversity and increasing crAssphage abundance, reflecting disrupted host-bacteriophage dynamics. No significant increase in clinically important ARGs was detected.DiscussionThese findings highlight the unpredictable and complex recovery of gut microbiota post-antibiotics. Individualized suspension periods in donor programs, guided by metagenomic analyses, are recommended to optimize FMT outcomes in various indications by considering antibiotic spectrum, duration, and host-specific factors.